Analysis of Market Retribution Management Systems in Efforts of Increasing Regional Original Income in The Office of Pd. Makassar Raya Market, Makassar City - Supiati Supiati; Andi Hafidah; Abdul Haeba Ramli (Business and Entrepreneurial Review, 2021)
Retribution is an important source of Regional Budget Revenue (PAD) in the city of Makassar. The budget charged by the Makassar City Government to the PD. Makassar Raya Market.This study aims to evaluate the management system of market levies and the contribution of market levies to increase Makassar City's Regional Original Income (PAD) and to formulate a more appropriate market levy management system to maximize PD revenue. Makassar Raya Market, Makassar City. The data used in this study are secondary in the form of documents and records related to market retribution income, and primary data in the form of daily reports of the recipient's cash-holding assistant as well as collection reports and proof of deposit of the recipient's treasurer into cash through the City Regional Development Bank (BPD). Makassar. The results of the study show that local revenue from market levies is in a very effective category, this is indicated by an average value of 100.28%, and Pasat Levies have a very large influence and contribution to Local Ownership in Makassar City, this can be shown by the average value of the contribution is 102.25%, while the growth rate of market levies explains that the growth rate with an average value is 9.69 which indicates the unsuccessful category The growth rate of market levies explains that the growth rate with an average value is 9.69 which indicates the unsuccessful category.